Computer safety, reliability, and security : SAFECOMP 2020 Workshops : DECSoS 2020, DepDevOps 2020, USDAI 2020, and WAISE 2020, Lisbon, Portugal, September 15, 2020, Proceedings /: SAFECOMP 2020 Workshops : DECSoS 2020, DepDevOps 2020, USDAI 2020, and WAISE 2020, Lisbon, Portugal, September 15, 2020, Proceedings. (2020) - Unknown
No abstract available